Pengaruh PSAK Syariah dan CSR terhadap Kepercayaan Investor dengan Mediasi Reputasi Perusahaan - Keisya Fitri Wulandari; Sri Rahayu; Lusi Elviani Rangkuti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
This study aims to examine the effect of the implementation of Sharia Financial Accounting Standards (PSAK Syariah) and Sharia-based Corporate Social Responsibility (CSR) disclosure on investor trust, with corporate reputation as a mediating variable in companies listed in the Sharia Securities List on the Indonesia Stock Exchange. This research employs a quantitative approach using secondary data obtained from annual reports and sustainability reports over the observation period. The sample consists of 16 companies with 48 observations, selected using purposive sampling. Data analysis is conducted using panel data regression combined with path analysis, and mediation testing is performed using the Sobel test. The results indicate that partially, the implementation of PSAK Syariah and Sharia CSR disclosure do not have a significant effect on investor trust. However, simultaneously, these variables along with corporate reputation have a significant effect on investor trust. Furthermore, PSAK Syariah and CSR disclosure have a positive effect on corporate reputation, but corporate reputation is not able to mediate the relationship between the independent variables and investor trust. These findings suggest that although companies have implemented Sharia principles in financial reporting and social responsibility, investors tend to prioritize financial performance indicators over Sharia compliance aspects in making investment decisions. This study implies that enhancing investor trust in the Islamic capital market requires not only compliance with Sharia accounting standards and CSR disclosure but also improvements in the quality, relevance, and transparency of financial information, as well as stronger integration between Sharia values and economic performance.